ANALYSIS OF BANK SOUNDNESS LEVEL USING RGEC METHOD (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL) AT PT BANK PEMBANGUNAN DAERAH JAWA TIMUR TBK FOR THE PERIOD OF 2020-2024 - Ika Atriyani Yanuar Mulatsih; Suryani Sri Lestari; Moh. Muslikh (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the soundness level of PT Bank Pembangunan Daerah Jawa Timur Tbk for the period 2020–2024 using the RGEC method, which consists of four assessment factors: Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital. This research uses secondary data in the form of annual financial statements, GCG self-assessment reports, and official publications from the Financial Services Authority (OJK). The Risk Profile analysis focuses on the Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) indicators. GCG is assessed based on self-assessment reports referring to POJK No. 55/POJK.03/2016 and POJK No. 17/POJK.03/2023. Earnings are measured using Return on Assets (ROA), Net Interest Margin (NIM), and the BOPO ratio, while Capital is evaluated using the Capital Adequacy Ratio (CAR). The results indicate that the Risk Profile is in the Sound to Very Sound category, with low NPL and LDR within a reasonable range. GCG obtained composite ratings between 2 (Sound) and 3 (Fair), Earnings showed fluctuations with declining ROA and NIM in 2023–2024, while BOPO remained sound. Capital consistently achieved the Very Sound category with CAR above the minimum requirement. The overall composite soundness ratings (CR) obtained consecutively from 2020 to 2024 were CR 2 (Sound), CR 1 (Very Sound), CR 2 (Sound), CR 1 (Very Sound), and CR 3 (Fairly Sound). Keywords: RGEC, Risk Profile, Good Corporate Governance, Earnings, Capital, Bank Jatim.